OVOZNI TANIB OLISH TIZIMLARI - Nurimov, P.B. (SCIENCE and SOCIETY, 2024)
In this article, voice recognition technology is considered as a promising direction of development with great potential for improving human-computer communication, increasing the safety and efficiency of control systems. To ensure the success and widespread use of the technology in the future, it is recommended that research and development continue, with particular attention to reliability and protection of user data.